Autophagy is associated with chemoresistance in neuroblastoma. Issue 1 (December 2016) - Belounis, Assila; Nyalendo, Carine; Le Gall, Roxane; Imbriglio, Tina; Mahma, Mohamed; Teira, Pierre; Beaunoyer, Mona; Cournoyer, Sonia; Haddad, Elie; Vassal, Gilles; Sartelet, Hervé
Abstract Background Neuroblastoma (NB) is a frequent pediatric tumor characterized by a poor prognosis where a majority of tumors progress despite intensive multimodality treatments. Autophagy, a self-degradative process in cells, could be induced by chemotherapy and be associated with chemoresistance. The aim of this study was to determine whether: 1) autophagy is present in NB, 2) chemotherapy modified its levels, and 3) its inhibition decreased chemoresistance. Methods Immunohistochemical stainings were performed on samples from 184 NB patients in order to verify the expression of LC3B, a specific marker for autophagy, and Beclin 1, a positive regulator of autophagy. In addition, we performed an in vitro study with six NB cell lines and six drugs (vincristine, doxorubicin, cisplatin temozolomide, LY294002 and syrolimus). Inhibition of autophagy was performed using ATG5 knockdown cells or hydroxychloroquine (HCQ). Cell survival was measured using the MTT cell proliferation assay. Autophagy was detected by monodansylcadaverine, confocal microscopy and Western blot. In vivo study with tumor xenografts in NSG mice was performed. Results Our results have indicated that autophagy was present at low levels in NB and was not a prognostic factor, while Beclin 1 was highly expressed in children with poor NB prognosis. However, autophagy levels increased after chemotherapy in vitro and in vivo. Tumor progression was significantly decreased in mice treated with a combination of HCQ and vincristine. Conclusions Taken together, autophagy is present in NB, induced by chemotherapy and associated with chemoresistance, which is significantly reduced by its inhibition. Therefore, targeting autophagy represents a very attractive approach to develop new therapeutic strategies in NB.